Peran Persepsi Ihsan, Egalitarianisme Islam, Persepsi Wakaf Uang, dan Kesadaran Wakaf Uang - Latifah Putranti; Ninditya Nareswari; Nuraini Desty Nurmasari (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2022)
This study examines the influence of perceived Ihsan, Islamic egalitarianism, perception of cash waqf, and awareness of cash waqf on cash waqf giving. The method used in this research is a survey using a questionnaire; there are 183 valid respondents in this study. This study used PLS-SEM to test the hypotheses, the result showed that people with high perceived Ihsan would have higher behavioural intention to help the other Muslims. Then, the higher the Islamic egalitarianism, the higher the individual's desire to achieve equality in the economic aspect of fellow Muslims. Furthermore, individuals with more heightened awareness and positive perceptions believe that waqf can help each other donate more through cash waqf.